Barriers to and facilitators of employment for people with psychiatric disabilities in Africa: a scoping review - I. D. Ebuenyi; E. V. Syurina; J. F. G. Bunders; B. J. Regeer (Taylor & Francis Group, 2018)
Background: Despite the importance of inclusive employment, described in Goal 8 of the Sustainable Development Goals (SDGs), employment of persons with psychiatric disabilities in Africa is lower than among the general population. Objective: The aim of this scoping review is to explore evidence related to the barriers to and facilitators of employment of persons with psychiatric disabilities in Africa. Methods: A literature search was conducted using six relevant electronic databases of articles published between 1990 and 2017. Results: Eight studies were identified and analysed regarding barriers and facilitators of employment of persons with psychiatric disabilities. The dynamic adaptation of the bio-psycho-social model was used as an analytical framework. Identified barriers include ill health, (anticipated) psychiatric illness, social stigma and discrimination, negative attitudes among employers and the lack of social support and government welfare. Facilitators of employment include stability of mental illness, heightened self-esteem, a personal decision to work despite stigma, competitive and supported employment, reduction in social barriers/stigma and workplace accommodations. Conclusion: Employment of persons with psychiatric disabilities is essential, yet there is dearth of scientific evidence to identify contextual models that might be useful in African countries and other low-and middle countries (LMICs). This gap in information would benefit from further research to improve the employment rates of persons with psychiatric disabilities in Africa.